Physiological Studies of Biosynthetic Indole Excretion in Bacillus alvei - Roth, C. W. (1971)
Bacillus alvei excretes indole during early exponential growth in acid-hydrolyzed casein medium. l-Threonine is the amino acid responsible for “early” indole excretion, and the amount of indole excreted is directly related to the amount of l-threonine in the medium. “Early-indole” excretion can be prevented by the continuous addition of serine (3.1 μmoles per ml per hr) or by substituting a mutant with an impaired ability to degrade serine. The addition of serine to a culture during the period of indole excretion halts the excretion and stimulates indole utilization. Threonine is a competitive inhibitor of serine (K(i) = 0.6 m) in the tryptophan synthetase B reaction. The internal tryptophan concentration increases during the period of indole excretion, suggesting that threonine acts by increasing the activity of the tryptophan pathway. This view is supported by experiments demonstrating that anthranilic acid and indoleacrylic acid also stimulate indole excretion. A metabolic explanation is offered and discussed.